1996
DOI: 10.2135/cropsci1996.0011183x003600030020x
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Response to Seasonal Patterns of Flower Removal: II. Growth and Dry Matter Allocation

Abstract: Development of a cotton (Gossypium hirsutum L.) crop is a full‐season process involving a complex balance between vegetative and reproductive allocation. Despite this fact, fruit removal studies have seldom examined the effects of flower removal during late anthesis. Flower removal treatments were imposed on two cotton cultivars to assess effects on vegetative and reproductive dry weights (DW) and boll maturation patterns. Flower removal treatments were imposed during early‐, mid‐, and late‐anthesis. Removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
6
15
1
Order By: Relevance
“…Moderate increases in biological yield (7.1%) and seed cotton yield (8.6%) were obtained under field conditions, although no yield advantage was found for potted plants. These results are in agreement with previous findings in which early reproductive sink removal increased the vegetative growth and favored more productive fruiting from later-developed positions to compensate for earlier losses (Kletter and Wallach 1982;Kennedy et al 1986;Ungar et al 1987;Jones et al 1996;Sadras 1996;Bednarz and Roberts 2001). Most importantly, the removal of early fruiting branches delayed the main-stem leaf senescence characterized by increase of chlorophyll concentration and photosynthetic activity of leaves.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moderate increases in biological yield (7.1%) and seed cotton yield (8.6%) were obtained under field conditions, although no yield advantage was found for potted plants. These results are in agreement with previous findings in which early reproductive sink removal increased the vegetative growth and favored more productive fruiting from later-developed positions to compensate for earlier losses (Kletter and Wallach 1982;Kennedy et al 1986;Ungar et al 1987;Jones et al 1996;Sadras 1996;Bednarz and Roberts 2001). Most importantly, the removal of early fruiting branches delayed the main-stem leaf senescence characterized by increase of chlorophyll concentration and photosynthetic activity of leaves.…”
Section: Discussionsupporting
confidence: 93%
“…Compensation for early fruit removal in cotton has been of great interest to both agronomists and entomologists, as it will not only help in establishing the recovery potential, but also provide a good experimental condition to study association between source and sink, as well as vegetative and reproductive growth (Dong et al 2008b;Zhang et al 2008). Numerous fruit removal studies have shown that reproductive sink removal enhances vegetative growth and development (Patterson et al 1978;Kennedy et al 1986;Ungar et al 1987;Jones et al 1996). Loss of early fruiting forms has also been shown to increase root growth (Sadras 1996;Dumka et al 2004), alter spatial yield distribution (Bednarz and Roberts 2001), and improve Cry1AC expression of transgenic Bacillus thuringiensis Berliner (Bt) cotton (Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The economic yield of cotton is basically influenced by the balance of assimilate allocation between vegetative and reproductive organs (Reta-Sánchez and Fowler, 2002;Jones et al, 1996;Kerby et al, 1993). In China, intensive farming technologies involving plastic mulching, plant topping and pruning have been widely adopted for cotton production in the last 40 years (Dai and Dong, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mid-season fruit loss may be less likely to be replaced. To fully compensate from mid-season square loss with minimum delay requires that more bolls on higher and more distal positions develop simultaneously after damage (Kennedy et al 1986, Jones et al 1996b, Bednarz and Roberts 2001. Our study showed a lower yield ranking for mid-season than early season fruit injury, indicating that some of the squares removed were not replaced.…”
Section: Discussionmentioning
confidence: 68%